Idiopathic aquagenic palmar keratoderma - Garofalo, L. (European Journal of Pediatric Dermatology, 2012)
A 4-year-old boy presented transient changes of the hands when dipped in water. The alterations were asymptomatic, starting one minute after immersion in water with a wrinkled appearance of the palmar surface, followed after 20 minutes by the appearance of small papules on the back of the hands and subsiding 20 minutes after the baby wiped his hands. The history was negative for taking drugs and cystic fibrosis, while there was generalized hyperhidrosis. After water immersion of the hands we saw before a wrinkled appearance of the palms (Fig. 1) and then monomorphic, whitish, approximately 2 mm in size papules on the dorsal surface of hands, prevailing at the metacarpophalangeal joints (Fig. 2). The final diagnosis was idiopathic aquagenic palmar keratoderma and iontophoresis was prescribed.